2018
DOI: 10.1007/s00345-018-2432-2
|View full text |Cite
|
Sign up to set email alerts
|

The cardiovascular risk factors in men with lower urinary tract symptoms

Abstract: Severity of LUTS and storage symptom significantly increases Framingham risk score, particularly with the components of total cholesterol level and age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…These results are echoed in an updated and more detailed analysis of 966 men with LUTS. 18 Yee et al 18 demonstrated that the severity of LUTS was significantly positively correlated with Framingham score, which is an estimate of the risk of coronary heart disease taking into account of age, sex, smoking status, cholesterol levels, blood pressure, and hypertensive treatments. This supports the hypothesis that atherosclerosis leads to pelvis and bladder ischaemia, and that this might be one of the mechanisms leading to LUTS.…”
Section: Discussionmentioning
confidence: 99%
“…These results are echoed in an updated and more detailed analysis of 966 men with LUTS. 18 Yee et al 18 demonstrated that the severity of LUTS was significantly positively correlated with Framingham score, which is an estimate of the risk of coronary heart disease taking into account of age, sex, smoking status, cholesterol levels, blood pressure, and hypertensive treatments. This supports the hypothesis that atherosclerosis leads to pelvis and bladder ischaemia, and that this might be one of the mechanisms leading to LUTS.…”
Section: Discussionmentioning
confidence: 99%
“…Since the MetS syndrome consists of a cluster of risk factors in cardiovascular diseases, atherosclerosis, through its related negative impact on bladder ischemia, is a potential mechanism for the development of OAB syndrome. In epidemiological studies, researchers reported that the severity of lower urinary tract symptoms is the risk factor of adverse cardiac events [ 40 ] and may increase the cardiovascular risk in terms of Framingham risk score [ 41 ], particularly in total cholesterol level. The vascular supply of the urinary bladder originates from the branches of the internal iliac artery, including superior, middle, and inferior vesical arteries.…”
Section: Chronic Bladder Ischemiamentioning
confidence: 99%
“…In Urology, we often fail to appreciate the greater picture of what men's health means. We focus expertly on diseases of the prostate and male genitourinary system, and increasingly their relationship to other organ systems, i.e., cardiovascular [1][2][3]. We now realize how metabolism and heart-health impact men's urinary and sexual function, and many urologists are screening for these non-urologic diseases [4][5][6][7][8].…”
Section: Dean Eltermanmentioning
confidence: 99%